Camera trapping reveals habitat overlap between snow leopards and common leopards in Gaurishankar Conservation Area, Nepal. : Habitat overlap between snow leopards and common leopards in Gaurishankar Conservation Area, Nepal - Chetri, Madhu; Ale, Purna Bahadur; Odden , Morten (Snow Leopard Reports, 2023)
We provide camera trap records of the presence of two large predators: the snow leopard Panthera uncia and common leopard Panthera pardus from the same habitats in Lapchi Valley of Gaurishankar Conservation Area. Camera traps were laid for 2,304 (mean 88.62 Å} SD 103.34) trap nights in 26 locations (elevation range: 2,140 to 4,350 m, area: 141.63 km2). A total of 55, 219 pictures were recorded from November 2022 to May 2023. Out of 26 camera stations, two camera stations captured the images of both species at an altitude of 4,000 m and 4,260 m in Lapchi Valley. The Relative Abundance Indices of snow leopards and common leopards were 7.51 SD 6.35 and 9.84 SD 6.35 per 100 trap days/nights, and independent detection rates were 0.41 and 0.52 respectively. This is the first evidence of habitat overlap between two large vulnerable predators in Gaurishankar Conservation Area. The nature of the coexistence or competition between these predators needs further investigation.